An Encounter Between Aristotle And Contemporary Philosophy of Mind The Case of Reductive Physicalism As Espoused By Jaegwon Kim - Ruttkamp-Bloem, Emma (University of Pretoria, 2020)
Thesis (DPhil)--University of Pretoria 2020.